MiR‐24‐3p enhances cell growth in hepatocellular carcinoma by targeting metallothionein 1M. (21st September 2016) - Dong, Xiaogang; Ding, Wei; Ye, Jianwei; Yan, Dong; Xue, Feng; Xu, Lin; Yin, Jiwei; Guo, Wenjia
Abstract : Dysregulation of microRNAs has been demonstrated to contribute to malignant progression of cancers, including hepatocellular carcinoma (HCC). MiR‐24‐3p was previously reported to be significantly upregulated in HCC. However, the potential role and mechanism of action of miR‐24‐3p in the initiation and progression of HCC remain largely unknown. Quantitative reverse transcription polymerase chain reaction demonstrated that miR‐24‐3p was significantly upregulated in HCC tumor tissues compared with nontumor tissues. The cell viability, colony formation assay, and tumorigenicity assays in nude mice showed that miR‐24‐3p could enhance HCC cell growth in vitro and in vivo. Metallothionein 1M was verified as an miR‐24‐3p target gene by using dual‐luciferase reporter assays, quantitative reverse transcription polymerase chain reaction, and Western blotting, which was involved in miR‐24‐3p regulated HCC cell growth. These results indicated that miR‐24‐3p plays an important role in the initiation and progression of HCC by targeting metallothionein 1M, and the miR‐24‐3p/metallothionein 1M pathway may contribute to the development of novel therapeutic strategies for HCC in the future.